(untitled) (Global Journals of Research in Engineering, 2022)
During the course of normal operation electrical components made from semiconducting materials undergo significant stress from heating This causes parts to wear out more quickly or in the more extreme cases fail altogether In order to maintain a stable operating temperature many different types of cooling systems have been used Our work investigates the best materials to use in these systems carefully considering effectiveness cost and longevity in our assessment Ansys simulation software was used to simulate the effects of different coolants on removing heat from a semiconductor The coolants are air water and aluminum oxide Though we didn t model the results of forced convection across these materials the natural convection heat transfer results in finding the more efficient coolant Considering liquid cooling methods for semiconductor-based devices the kind of fluid plays a vital role in the transfer of energy The Aluminum Oxide was selected in a 2 solution and 40nm wide particles to simulate for our nanofluid as it is commonly used in the industry and data for it was readily available The aluminum oxide nanofluid had the best cooling performance of the three tested materials